2014
DOI: 10.4081/ijas.2014.3168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Administration of Chlorella on the Immune Status of Gibel Carp, Carassius Auratus Gibelio

Abstract: In the present study the effects of dietary Chlorella on the immune status of gibel carp, Carassius auratus gibelio, were evaluated. A total of 540 healthy fish were divided into 6 groups, with one control group fed with Chlorella-free diet and five experimental groups fed diets supplemented with 0.4 to 2.0% Chlorella. The whole trial lasted 60 days. At the end of the trial, the weight gain and immune parameters of fish were analysed. Results showed that Chlorella could increase the levels of immunoglobulin M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…C. vulgaris , like many other microalgae, is known to possess a number of immunostimulants in the form polysaccharides, which are substances that induce immune activity in different animals (Huang, Zhou & Zhang ). Its ability to improve immune function has been already proven in gibel carps (Zhang, Giu, Xu, Gao, Shao & Qi ). Chlorella extract was also reported to increase resistance of Plecoglossus altivelis against Vibrio anguillarium (Bergeman) (Nakagawa, Kumai, Nakagawa & Kasahara ), but information is lacking in other aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…C. vulgaris , like many other microalgae, is known to possess a number of immunostimulants in the form polysaccharides, which are substances that induce immune activity in different animals (Huang, Zhou & Zhang ). Its ability to improve immune function has been already proven in gibel carps (Zhang, Giu, Xu, Gao, Shao & Qi ). Chlorella extract was also reported to increase resistance of Plecoglossus altivelis against Vibrio anguillarium (Bergeman) (Nakagawa, Kumai, Nakagawa & Kasahara ), but information is lacking in other aquatic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . () observed an increase in IgM, IgD, Interleukin‐22 (IL‐22) and chemokine levels at low‐level dietary supplementation (0.4–1.2% kg −1 ) of Chlorella sp. They further observed that the microalga might be involved in regulating fish innate and adaptive immunity, immunostimulatory mediators and gene expression.…”
Section: Chlorella Vulgaris In Fish and Crustaceans Immunitymentioning
confidence: 99%
“…Moreover, it showed better activity in inhibiting lipid peroxidation as compared to glutathione and has antioxidant properties (Bengwayan et al, ). Zhang et al () found that Chlorella could significantly increase the serum IgM and IgD levels of gibel carp and thus play role in the mucosal immunity. Another study investigated the effect of replacement of fish meal by Chlorella meal supplemented to crucian carp, Carassius auratus and after evaluation of the growth performance, digestive enzymatic activities, histology and myogenic genes’ expression, the authors concluded that Chlorella meal could totally replace the fishmeal (Shi et al, ).…”
Section: Introductionmentioning
confidence: 99%